Pancasila and the Long Shadow of Suharto's Authoritarianism, 1966-1998 - Karjono, Karjono; Riyanto, Benny; Kurniawan, Edi; Nayan, Nasir (History Department, Semarang State University and Historian Society of Indonesia, 2024)
Abstract: This paper aims to analyze the history of the development of the political interpretation of Pancasila under Suharto's authoritarian rule between 1966 and 1998. The research questions are: 1) how did Pancasila become the ideological basis for authoritarian power? 2) How did Pancasila become the basis for pseudo-democracy during the Suharto government? This research used historical methods, relying on data from archives and newspapers from 1966 to 1998. Analysis of this research data used Historical Discourses Analysis (HDA). The findings show that Pancasila, at the beginning of the Suharto government, was trying to be cleansed of the influence of Sukarno and communism. In this period, Pancasila was reinterpreted. The success of the Suharto government in reinterpreting Pancasila was due to de-sukarnoization efforts and strict control over elements of society. In subsequent developments, Pancasila became the label and slogan in every government policy, the most famous of which was 'Pancasila Democracy', a system designed to show that the Suharto government was the savior and protector of Pancasila, which can be considered a pseudo-democracy. This democratic system does not prioritize freedom of expression and political autonomy of society. Research regarding the political interpretation of Pancasila will continue to be carried out to analyze the extent to which this idea can continue to be relevant in application in Indonesia. Abstrak: Tujuan penelitian ini adalah untuk menganalisis sejarah perkembangan politik penafsiran Pancasila pada masa pemerintahan otoriter Soeharto antara tahun 1966 sampai dengan tahun 1998. Pertanyaan penelitiannya adalah: 1) bagaimana Pancasila menjadi dasar ideologis kekuasaan otoriter? 2) Bagaimana Pancasila menjadi dasar demokrasi semu pada masa pemerintahan Soeharto? Penelitian ini dilakukan dengan menggunakan metode historis, dengan mengandalkan data dari arsip dan surat kabar tahun 1966 sampai dengan tahun 1998. Analisis data penelitian ini menggunakan Historical Discourses Analysis (HDA). Hasil temuan penelitian menunjukkan bahwa Pancasila pada awal pemerintahan Soeharto sedang berusaha dibersihkan dari pengaruh Sukarno dan komunisme. Pada periode ini, Pancasila diinterpretasikan ulang. Keberhasilan pemerintahan Soeharto dalam melakukan reinterpretasi Pancasila tidak lepas dari upaya de-sukarnoisasi dan kontrol yang ketat terhadap elemen masyarakat. Dalam perkembangan selanjutnya, Pancasila menjadi label dan slogan dalam setiap kebijakan pemerintah, yang paling terkenal adalah 'Demokrasi Pancasila', sebuah sistem yang dirancang untuk menunjukkan bahwa pemerintahan Soeharto adalah penyelamat dan pelindung Pancasila, yang dapat dianggap sebagai demokrasi semu. Sistem demokrasi ini tidak mengutamakan kebebasan berekspresi dan otonomi politik masyarakat. Penelitian mengenai interpretasi politik Pancasila akan terus dilakukan untuk menganalisis sejauh mana gagasan ini dapat terus relevan dalam penerapannya di Indonesia.